Large‐scale isolation and cytotoxicity of extracellular vesicles derived from activated human natural killer cells. Issue 1 (1st December 2017) - Jong, Ambrose Y.; Wu, Chun‐Hua; Li, Jingbo; Sun, Jianping; Fabbri, Muller; Wayne, Alan S.; Seeger, Robert C.
ABSTRACT: Extracellular vesicles (EVs) have been the focus of great interest, as they appear to be involved in numerous important cellular processes. They deliver bioactive macromolecules such as proteins, lipids, and nucleic acids, allowing intercellular communication in multicellular organisms. EVs are secreted by all cell types, including immune cells such as natural killer cells (NK), and they may play important roles in the immune system. Currently, a large‐scale procedure to obtain functional NK EVs is lacking, limiting their use clinically. In this report, we present a simple, robust, and cost‐effective method to isolate a large quantity of NK EVs. After propagating and activating NK cells ex vivo and then incubating them in exosome‐free medium for 48 h, EVs were isolated using a polymer precipitation method. The isolated vesicles contain the tetraspanin CD63, an EV marker, and associated proteins (fibronectin), but are devoid of cytochrome C, a cytoplasmic marker. Nanoparticle tracking analysis showed a size distribution between 100 and 200 nm while transmission electron microscopy imaging displayed vesicles with an oval shape and comparable sizes, fulfilling the definition of EV. Importantly, isolated EV fractions were cytotoxic against cancer cells. Furthermore, our results demonstrate for the first time that isolated activated NK (aNK) cell EVs contain the cytotoxic proteins perforin, granulysin, and granzymes A and B, incorporated from the aNK cells. Activation of caspase ‐3, ‐7 and ‐9 was detected in cancer cells incubated with aNK EVs, and caspase inhibitors blocked aNK EV‐induced cytotoxicity, suggesting that aNK EVs activate caspase pathways in target cells. The ability to isolate functional aNK EVs on a large scale may lead to new clinical applications. Abbreviations : NK: natural killer cells; activated NK (aNK) cells; EVs: extracellular vesicles; ALL: acute lymphoblastic leukaemia; aAPC: artificial antigen‐presenting cell; TEM: transmission electron microscope; PBMC: peripheral blood mononuclear cells; FBS: foetal bovine serum.